Parameter search of a CPG network using a genetic algorithm for a snake robot with tactile sensors moving on a soft floor - Tamura, Hajime; Kamegawa, Tetsushi (Frontiers in Robotics and AI, 2023)
When a snake robot explores a collapsed house as a rescue robot, it needs to move through various obstacles, some of which may be made of soft materials, such as mattresses. In this study, we call mattress-like environment as a soft floor, which to be deformed when some force is added to it. We focused on the central pattern generator (CPG) network as a control for the snake robot to propel itself on the soft floor and constructed a CPG network that feeds back contact information between the robot and the floor. A genetic algorithm was used to determine the parameters of the CPG network suitable for the soft floor. To verify the obtained parameters, comparative simulations were conducted using the parameters obtained for the soft and hard floor, and the parameters were confirmed to be appropriate for each environment. We also confirmed that the effectiveness of the tactile sensor was considered in the parameter search by observing the difference in snake robot's propulsion depending on the presence or absence of the tactile sensor feedback signal.